EXTENDED TRAFFIC CRASH MODELLING THROUGH PRECISION AND RESPONSE TIME USING FUZZY CLUSTERING ALGORITHMS COMPARED WITH MULTI-LAYER PERCEPTRON - Aghayan, Iman; Noii, Nima; Kunt, Mehmet Metin (Sveuciliste U Zagrebu, Fakultet Prometnih Znanosti, 2012)
This paper compares two fuzzy clustering algorithms - fuzzy subtractive clustering and fuzzy C-means clustering - to a multi-layer perceptron neural network for their ability to predict the severity of crash injuries and to estimate the response time on the traffic crash data. Four clustering algorithms - hierarchical, K-means, subtractive clustering, and fuzzy C-means clustering - were used to obtain the optimum number of clusters based on the mean silhouette coefficient and R-value before applying the fuzzy clustering algorithms. The best-fit algorithms were selected according to two criteria: precision (root mean square, R-value, mean absolute errors, and sum of square error) and response time (t). The highest R-value was obtained for the multi-layer perceptron (0.89), demonstrating that the multi-layer perceptron had a high precision in traffic crash prediction among the prediction models, and that it was stable even in the presence of outliers and overlapping data. Meanwhile, in comparison with other prediction models, fuzzy subtractive clustering provided the lowest value for response time (0.284 second), 9.28 times faster than the time of multi-layer perceptron, meaning that it could lead to developing an on-line system for processing data from detectors and/or a real-time traffic database. The model can be extended through improvements based on additional data through induction procedure.
Keywords: fuzzy subtractive; fuzzy C-means; hierarchical clustering; K-means clustering; multi-layer perceptron; traffic crash severity